Spatially resolved spectroscopy across stellar surfaces: IV. F, G, and K-stars: synthetic 3D spectra at hyper-high resolution - Dravins, Dainis; Ludwig, Hans-Günter; Freytag, Bernd (Astronomy and astrophysics, 2021)
Context. High-precision stellar analyses require hydrodynamic 3D modeling. Such models predict changes across stellar disks of spectral line shapes, asymmetries, and wavelength shifts. For testing models in stars other than the Sun, spatially resolved observations are feasible from differential spectroscopy during exoplanet transits, retrieving spectra of those stellar surface segments that successively become hidden behind the transiting planet, as demonstrated in Papers I, II, and III. Aims. Synthetic high-resolution spectra over extended spectral regions are now available from 3D models. Similar to other ab initio simulations in astrophysics, these data contain patterns that have not been specifically modeled but may be revealed after analyses to be analogous to those of a large volume of observations. Methods. From five 3D models spanning Teff = 3964-6726 K (spectral types ~K8 V-F3 V), synthetic spectra at hyper-high resolution (λ/Δλ >1 000 000) were analyzed. Selected Fe I and Fe II lines at various positions across stellar disks were searched for characteristic patterns between different types of lines in the same star and for similar lines between different stars. Results. Spectral-line patterns are identified for representative photospheric lines of different strengths, excitation potentials, and ionization levels, thereby encoding the hydrodynamic 3D structure. Line profiles and bisectors are shown for various stars at different positions across stellar disks. Absolute convective wavelength shifts are obtained as differences to 1D models, where such shifts do not occur.Conclusions. Observable relationships for line properties are retrieved from realistically complex synthetic spectra. Such patterns may also test very detailed 3D modeling, including non-LTE effects. While present results are obtained at hyper-high spectral resolution, the subsequent Paper V examines their practical observability at realistically lower resolutions, and in the presence of noise.
Gesehen am 02.03.2022